Gender-Based Violence : An Analysis of the Implications for the Nigeria for Women Project - World Bank (Washington, DC: World Bank, 2019)
Gender-based violence, or GBV, is one of the most oppressive forms of gender inequality, posing a fundamental barrier to the equal participation of women and men in social, economic, and political spheres. GBV includes intimate partner violence, non-partner sexual assault, female genital mutilation, sexual exploitation and abuse, child abuse, female infanticide, and child marriage. Such violence impedes gender equality and the achievement of a range of development outcomes. In Nigeria, like in other jurisdictions, GBV remains a challenge that significantly constrains women’s autonomy and opportunities. Conflict in Nigeria’s North East geopolitical zone has further contributed to a steep rise in violence targeted against women and children by Boko Haram. This report uses the social ecological model as the basis to analyze prevalent GBV risks in Nigeria. It first describes the legislative and policy level frameworks associated with violence against women and girls as well as their implementation at the national and subnational levels. It then provides a detailed analysis of specific social norms that have created acceptance for or at least a lack of condemnation of GBV at the community level. Finally, based on field research, it delves deeper into some of the interpersonal and individual drivers of various forms of GBV in the selected communities.